Wastewater treatment by a prototype slow rate land treatment system - Jenkins, T. F.; Palazzo, T. F.; U.S. Army Cold Regions Research and Engineering Laboratory.; United States. Army. Office of the Chief of Engineers. (Hanover, N.H. : U.S. Army Cold Regions Research and Engineering Laboratory, 1981)
Prepared for Directorate of Civil Works - Office of the Chief of Engineers / by Corps of Engineers, U.S. Army Cold Regions Research and Engineering Laboratory, under DA Project 4A762720A896. August 1981. Cover title. Literature cited: p. 37-39. Mode of access: Internet.